2014
DOI: 10.1093/icesjms/fsu129
|View full text |Cite
|
Sign up to set email alerts
|

Environmental requirements for three sea pen species: relevance to distribution and conservation

Abstract: The aim is to determine the environmental requirements, estimate the extent of suitable habitat for three sea pen species, and assess the implications for marine protected areas (MPAs). The sea pen Funiculina quadrangularis and the habitat associated with two further sea pen species, Virgularia mirabilis and Pennatula phosphorea, are of key conservation importance and are recommended for protection within MPAs. This study models their potential distributions using the MAXimum ENTropy algorithm and assesses the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…For instance, several species of sea pens in Scottish marine waters are abundant in mud and become rare or, ultimately, absent as the amount of gravel increases [21]. As noted before, it is possible that currents, playing over the cables, can distribute sediments based on grain size, thus leading to coarser sediments on one side and finer ones on the other.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several species of sea pens in Scottish marine waters are abundant in mud and become rare or, ultimately, absent as the amount of gravel increases [21]. As noted before, it is possible that currents, playing over the cables, can distribute sediments based on grain size, thus leading to coarser sediments on one side and finer ones on the other.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of studies is limited, sea pens appear to have fewer associated organisms compared to scleractinians and gorgonians. Funiculina quadrangularis is a species with greatest conservation importance in the greater North Sea and Celtic Sea areas [78]. It can become a little more than 2 m tall, with approximately one quarter of the lower part of the structure embedded in the sediment [78].…”
Section: Sea Pen Medowsmentioning
confidence: 99%
“…Funiculina quadrangularis is a species with greatest conservation importance in the greater North Sea and Celtic Sea areas [78]. It can become a little more than 2 m tall, with approximately one quarter of the lower part of the structure embedded in the sediment [78]. Predators on sea pens include nudibranchs, which have been observed preying on sea pen polyps.…”
Section: Sea Pen Medowsmentioning
confidence: 99%
“…are known to be much stouter and fleshier than F. quadrangularis (Manuel 1981), which probably helps them to settle in less homogeneous sediments. In fact, both species are known to occur in muddy substrata, but Manuel (1981) also reported P. phosphorea in sandy substrata and Greathead et al (2015) reported the absence of F. quadrangularis in sediment with gravel content above 30%.…”
Section: Aggregations Of Pennatula Spp On Circalittoral Soft Bottomsmentioning
confidence: 99%